Phytoremediation, when plant species biological cycle is the key to success - Pérez Cuadra, Vanesa (2024)
The contamination of different substrates with diverse types of substances urgently requires theapplication of processes that allow them to be completely removed or, at least, greatly reduced. Theapplication of phytoremediation systems is a viable option in many cases. Plant species present different characteristics throughout their life cycle which, if used appropriately, allow the extraction process to be more efficient. Studying and interpreting phytoremediation species as complex systems is key to the success of the process.